1981
DOI: 10.1118/1.594999
|View full text |Cite|
|
Sign up to set email alerts
|

Perturbation of electron beam doses as a function of SSD due to the use of shielding blocks on the Clinac-18

Abstract: Many radiotherapy linear accelerators use electron beam applicators which extended close to the patient's surface when treating at the regular distance. The relatively large size of these applicators often necessitates the use of a larger SSD than that designed by the manufacturer. In such cases, the addition of shielding blocks to the applicator can significantly alter the factors which should be used to calculate the dose rate at the new SSD as compared with the unshielded beam condition. In some typical cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This method represents an alternative approach to the effective SSD method, using the same set of measured data. Both methods are consistent with the suggestion of Thomadsen et al (1981) to measure any output at an extended distance, as they both provide a methodology for storing and using the data.…”
Section: Correction Of Outputsupporting
confidence: 73%
“…This method represents an alternative approach to the effective SSD method, using the same set of measured data. Both methods are consistent with the suggestion of Thomadsen et al (1981) to measure any output at an extended distance, as they both provide a methodology for storing and using the data.…”
Section: Correction Of Outputsupporting
confidence: 73%
“…For a given applicator, there is a strong dependence of SSD eff on insert size. 109 Investigators have shown that SSD eff is only weakly dependent on the applicator 40,110 so tables of SSD eff versus insert size are clinically adequate. In fact, Sharma and Johnson 111 suggested that a single SSD eff for each energy can be used for field sizes larger than 10 × 10 cm 2 .…”
Section: B2d Effectivementioning
confidence: 99%
“…Physical limitations in the treatment set-up mean that high-energy electron therapy may be given at extended source-surface distances (SSD) (Thomadsen et al 1981). Irregularities of the skin surface may also create air gaps or minor areas of the field at extended SSD, which affect the absorbed dose, although the SSD effect may be minor compared with that of surface scatter.…”
Section: Introductionmentioning
confidence: 99%